2006
DOI: 10.1111/j.1551-2916.2006.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Loops in Pressureless‐Sintered Undoped BaTiO3 Ceramics

Abstract: Dislocation loops in pressureless‐sintered undoped BaTiO3 ceramics have been analyzed by transmission electron microscopy. The Burgers vector of the loops and its sense b=+1/2[010] were determined using the g·b=0 invisibility criteria, combined with the inside–outside contrast technique using (g·b)sg>0 or<0, keeping the deviation parameter sg>0. The edge‐vacancy nature was further ascertained by determining the loop habit plane normal n=[010]. Weak‐beam dark‐field imaging reveals that loops contained no stacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The individual dislocations in Figure D and the dislocation structures in (F) verify that it is possible to introduce dislocations by plastic deformation of BaTiO 3 . Previous TEM analyses have demonstrated that different types of dislocations can be induced in BaTiO 3 ‐based materials . Figure D reveals typical dislocations loops with scallops along the dislocation line .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The individual dislocations in Figure D and the dislocation structures in (F) verify that it is possible to introduce dislocations by plastic deformation of BaTiO 3 . Previous TEM analyses have demonstrated that different types of dislocations can be induced in BaTiO 3 ‐based materials . Figure D reveals typical dislocations loops with scallops along the dislocation line .…”
Section: Resultsmentioning
confidence: 86%
“…Suzuki et al argued that these loops arise due to vacancy condensation and require the presence of Schottky defects (eg, VitalicBa,VitalicTi,VO) . Additionally, it was proven that dislocations can adorn domain walls . and that the density of the dislocation loops can be influenced by oxygen partial pressure …”
Section: Resultsmentioning
confidence: 99%
“…In Al alloys, thermal vacancies are known to condense to prismatic dislocation loops upon quenching to room temperature 29 . Indeed, vacancy loops in BaTiO 3 were often found in MLCC chips, 30 in undoped BaTiO 3 , 31 and in MgO doped BaTiO 3 32 sintered in air. Two types of loops are formed with an identical Burgers vector b =1/2 〈010〉 31 via the condensation of (i) and (i.e., vacant BaO‐layer), and (ii) and (i.e., vacant TiO 2 layer) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vacancy loops in BaTiO 3 were often found in MLCC chips, 30 in undoped BaTiO 3 , 31 and in MgO doped BaTiO 3 32 sintered in air. Two types of loops are formed with an identical Burgers vector b =1/2 〈010〉 31 via the condensation of (i) and (i.e., vacant BaO‐layer), and (ii) and (i.e., vacant TiO 2 layer) 30 . Vacancies in the stoichiometric composition are required at the sites where loops are formed, and the slower moving species (Ba 2+ or Ti 4+ ) is rate‐controlling kinetically in forming loops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation